FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI DINAS PENDIDIKAN NASIONAL KABUPATEN MUSI BANYUASAIN - Kunardi, Kunardi; Fatimah, Fatimah (Jurnal Ilmu Manajemen, 2012)
The purpose of this research is to find out the influence compensation, job placement and work enviroment of employee satisfaction of Dinas Pendidikan Nasional Kabupaten Musi Banyuasin. In this research used four variables are compensation, job placement, enviroment work as variabel influence and employee satisfaction as variables that influenced. Each variables developing become some indicators as basis for making the questionnaire as device to collect data. So not only primer data as most needed data but also secondary data as completeness. For the resources used 54 sampels that selected with stratified sampling. This research using multiple linier regression. After validity test, reliability test, normality test, and classical assumption test, the analysis of data obtained. The result of this analysis showing that there are significant influence together and parcial from compensation variable (0,362), job placement (0,416), and work enviroment (0,311) of employee satisfcation of Dinas Pendidikan Nasional Kabupaten Musi Banyuasin.